Impact of Influencer Marketing on the Buying Behavior of Youth - Ayesha Ishfaq; Fahad Anis (`, 2026)
Influencer marketing is when businesses collaborate with internet influencers to sell their goods. Because influencers have sizable internet and social media followings, other influencer marketing partnerships are less tangible. Some individuals have millions or even hundreds of thousands of followers. Many of them will still probably seem like regular individuals. They might only have a thousand followers, or in certain situations, even less. These are the people who create the most engaging social media posts, depending on their area of expertise. They produce the most thrilling films, publish the most exquisite content, and conduct the most engaging and educational online discussions. This thesis aims to investigate the popularity of Instagram influencers, the effectiveness of influencer marketing in promoting a particular product, and the potential of influencer marketing in the marketing industry. The study also looks at the causes behind consumers buying behavior, consumer attraction towards products. To accomplish this study’s goals, we used quantitative data using an objective approach. Survey questionnaire was conduct from the students of different universities two private sector universities (University of Management and Technology, University of Central Punjab) and two government universities (The University of Punjab, Government College & University). Sample size for this study was 600 which is divided as on 150 from each university. All our hypothesis were supported. Influencer marketing has a major positive impact on young people’s purchasing decisions and greatly increases product promotion. Purchase intent is boosted by the opinions of influencers, strong post interaction, and encouraging audience comments. Youth judgements are also greatly influenced by the kind and quality of information. Keywords: Influencer Marketing, Consumer Buying Behavior, Social Media, Youth, Pakistan.